1997
DOI: 10.1046/j.1365-3083.1997.d01-92.x
|View full text |Cite
|
Sign up to set email alerts
|

IL‐10 Plays a Role in the Modulation of Human Granulomatous Hypersensitivity Against Schistosoma mansoni Eggs Induced by Immune Complexes

Abstract: Rezende SA, Silva-Teixeira DN, Drummond SC, Goes AM. IL-10 Plays a Role in the Modulation of Human Granulomatous Hypersensitivity Against Schistosoma mansoni Eggs Induced by Immune Complexes. Scand J Immunol 1997;46:96-102 It has been demonstrated that the chronic intestinal form of schistosomiasis is associated with the establishment and maintenance of a variety of immunoregulatory mechanisms that lead to a diminished granulomatous reaction to parasite eggs. Using an in vitro model of granuloma reaction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 17 publications
(36 reference statements)
3
12
0
Order By: Relevance
“…A stronger PBMC proliferation against SAWA than SEA was demonstrated. This is in agreement with several reports of a lower response to SEA in comparison with SWAP in chronic schistosomiasis (Freeman et al 1983;Colley et al 1986;Roberts et al 1993;Viana et al 1994;Bahia-Oliveira et al 1996;Rezende et al 1997). It has been suggested that the lower proliferative response against SEA observed in the chronic phase of the disease is due to modulation of the cellular response against eggs with the progression of the infection .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A stronger PBMC proliferation against SAWA than SEA was demonstrated. This is in agreement with several reports of a lower response to SEA in comparison with SWAP in chronic schistosomiasis (Freeman et al 1983;Colley et al 1986;Roberts et al 1993;Viana et al 1994;Bahia-Oliveira et al 1996;Rezende et al 1997). It has been suggested that the lower proliferative response against SEA observed in the chronic phase of the disease is due to modulation of the cellular response against eggs with the progression of the infection .…”
Section: Discussionsupporting
confidence: 92%
“…Adult worms induce a Th1-type cytokine profile with elevated levels of IFN-γ, IL-12, and TNF-α (Grzych et al 1991;Leptak and McKerrow 1997). In accordance with our results, Rezende et al (1997) observed an elevation of TNF-α in in vitro granuloma formation and cell proliferation assays when PBMC from chronic INT patients were stimulated with S. mansoni egg antigens. In contrast, high levels of TNF-α were found in the circulation of patients with hepatosplenic schistosomiasis (Zwingenberger et al 1990;Mwatha et al 1998).…”
Section: Discussionsupporting
confidence: 92%
“…Table 2 shows the effects on HG size of introduction during infection of blocking antibodies to some cytokines and cytokine receptors. By this criterion, IL-2 (22), TNF-␣ (71), and the IFN-␥ receptor (119) in S. mansoni-infected mice and IL-5 (28) and the IL-2 receptor (27) in S. japonicum-infected mice participated in HG pathogenesis. In S. mansoni-infected mice IL-2 (22), IL-5 (125), IL-10 (15, 40), IFN-␥ (125), and the IFN-␥ receptor (119) and in S. japonicum-infected animals the IL-2 receptor (27) were also involved in determining the cellular composition of the HG.…”
Section: Granuloma Formationmentioning
confidence: 99%
“…By this criterion, IL-2 (22), TNF-␣ (71), and the IFN-␥ receptor (119) in S. mansoni-infected mice and IL-5 (28) and the IL-2 receptor (27) in S. japonicum-infected mice participated in HG pathogenesis. In S. mansoni-infected mice IL-2 (22), IL-5 (125), IL-10 (15, 40), IFN-␥ (125), and the IFN-␥ receptor (119) and in S. japonicum-infected animals the IL-2 receptor (27) were also involved in determining the cellular composition of the HG. Table 3 shows that the introduction during infection of some recombinant cytokines, including recombinant IL-2 (91), recombinant IL-7 (146), and recombinant TNF-␣ (3, 71), enhanced HG size.…”
Section: Granuloma Formationmentioning
confidence: 99%
“…Furthermore, an opposite effect was seen in IL-10-deficient mice . Rezende et al (1997) suggested that immunocomplexes from patients with chronic intestinal schistosomiasis are able to modulate granulomatous hypersensitivity to S. mansoni eggs by inducing prostaglandin E production that augments IL-10 levels. Cytokines are believed to modulate the amount of fibrosis and granuloma size and to play a fundamental role in the pathology of schistosome infection.…”
Section: Discussionmentioning
confidence: 99%